2014
DOI: 10.15274/nrj-2014-10024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Arterial Injuries after Penetrating Brain Trauma Based on Scoring Signs from Emergency CT Studies

Abstract: SUMMARY -The objective of this study was to determine the accuracy of individual radiologists in detection of vascular injury in patients after penetrating brain injury (PBI) based on head CT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…7,8 Early detection and treatment of traumatic pseudoaneurysms would thus prevent secondary injury through haemorrhage. 9 A 12% incidence of traumatic pseudoaneurysms following stab head has previously been reported in our department. The same study also showed a mortality rate of 26% for patients who presented with the blade removed compared with 11% for those with the blade in place.…”
Section: Discussionmentioning
confidence: 73%
“…7,8 Early detection and treatment of traumatic pseudoaneurysms would thus prevent secondary injury through haemorrhage. 9 A 12% incidence of traumatic pseudoaneurysms following stab head has previously been reported in our department. The same study also showed a mortality rate of 26% for patients who presented with the blade removed compared with 11% for those with the blade in place.…”
Section: Discussionmentioning
confidence: 73%
“…Self-inflicted gunshot wounds are a rare event and a significant portion of these patients have their care terminated in the prehospital setting or in the trauma bay 24 . Thus the sample size is relatively small, which inherently limits any post hoc analysis of mortality/survival and other risk factors for vascular injury such as wound penetration near the Sylvian fissure and crossing of multiple dural compartments 3,25–27 . We are also not able to provide pertinent insight into subsequent management of CVIs largely due to the fact that conventional anticoagulation or antiplatelet treatment utilized in BCVIs would be acutely contra-indicated due to the risk of worsening intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 98%
“…24 Thus the sample size is relatively small, which inherently limits any post hoc analysis of mortality/survival and other risk factors for vascular injury such as wound penetration near the Sylvian fissure and crossing of multiple dural compartments. 3,[25][26][27] We are also not able to provide pertinent insight into subsequent management of CVIs largely due to the fact that conventional anticoagulation or antiplatelet treatment utilized in BCVIs would be acutely contraindicated due to the risk of worsening intracerebral hemorrhage. Nonetheless, we have observed a strong association of not only CVIs, but distant CVIs within the SIGSW population and, therefore, we believe that these CVIs need to be screened for and found.…”
Section: Discussionmentioning
confidence: 99%
“…The implication of all studies of GCS in deaths led Rish et al [16] as well as Levy et al [45] or Lieberman et al [46] to say that any patient admitted for PCCW with a GCS ≤ 5 had no reasonable chance of survival and should abstain from any surgical procedure. According to these three authors, including Bodanapally et al [15] the presence of SA hemorrhage was to be considered a significant factor associated with mortality. In addition to these clinical and therapeutic risk factors, which involved all causes of PCCW without distinction, there are also parameters that are sometimes specific to intracerebral gunshot PCCW.…”
Section: Discussionmentioning
confidence: 99%